“A case study evaluating the effectiveness of adherence clubs in Gugulethu as a strategy for mobilizing and engaging men in HIV treatment” - Ncube, Petronella (Department of Public Health and Family Medicine, 2022)
The existing global literature shows that men living with HIV need efficient antiretroviral treatment (ART) delivery. Adherence clubs (ACs) have been identified as one way to improve retention of stable patients living with Human Immunodeficiency Virus (HIV). ACs are among several strategies that have been said to potentially assist in the engagement and mobilization of men in HIV services. However, very few have been evaluated to see whether they are effective in this regard. This qualitative study examines the facilitating factors that help retain and engage men in HIV services by trying to understand the perceived effectiveness of the Adherence Club in Gugulethu. The study employs a qualitative approach to explore the facilitating factors which help retain and engage men in HIV services. A total of 12 participants participated in in-depth telephonic interviews. The participants included stakeholders of the AC such as the health workers (facilitators, nurse, community health worker (CHW) and adherence counsellors), men attending the club and family members who are indirectly involved in supporting participants engagement in the AC as patients. Interviews were conducted in IsiXhosa and for data analysis, they were translated to English, and a thematic analysis was done. The findings show facilitating factors in all stages of the socio-ecological model with the patient level being the vital stage which allows for the integration of other level factors. This study shows that when men properly utilize the different resources provided for their HIV treatment, their engagement and retention in the AC improves. It is therefore key for policy makers to consider planning for male-focused health services to ensure that men view health services as spaces which are inclusive and tailored for them to improve their engagement and retain them in health services.